Analisa Perbandingan Kinerja Keuangan Sebelum dan Setelah Pemutusan Hubungan Kerja - Defel Septian; Khairunnisa; Ni Putu Diana Purnami Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to test and analyze financial ratios before and after the termination of PT Indosat Tbk employment eith the variables liquidity ratio, solvency ratio, profitability ratio and activity ratio. The research method used is a quantitative analysis method. The type of data is secondary data. The ratios to measure PT Indosat financial performance are curret ratio, quick ratio, cash ratio, debt to asset ratio, debt to equity ratio, net profit margin, return on asset, total asset turnover. analysis of this research data was done using the data normality test, hypothesis testing using the paired sample t-test and the Wilcoxon signed rank test. The result of this research show that indosat performance is in poor condition and it is sated that there is no significant difference in the company performance using the indicators current ratio, quick ratio, cash ratio, debt to equity ratio, net profit margin, return on asset, total aset turnover.